Assessment of medicinal folklores and chemical composition of Aerva javanica (Burm. f.) Juss. ex Schult. in Cholistan Desert of Pakistan - Azhar, Muhammad Farooq; Aziz, Abida; Ali, Ehsan (Ethnobotany Research and Applications, 2022)
Background: The desert ecosystem of Cholistan is rich in xerophytic flora of medicinal importance. Aerva javanica is most common shrub and equally neglected as potential medicinal plant in the study area. Chemical composition as well as medicinal folklores of Aerva javanica in the Cholistan desert of Pakistan was explored in this study. Methods: Data was collected through questionnaires by interviewing local inhabitants and herbal practitioners and direct observations during field surveys. A total of 320 respondents of various age groups were selected randomly for household survey and medicinal plants experts (n=14) were interviewed by using snowball method for validating medicinal uses. Whole plant including leaves, flowers and tender shoots was sampled. Nutritive and phytochemical attributes were analyzed. Results: The plant use inventory of this plant showed that local inhabitants used this shrub as firewood, fodder, making huts and as human and veterinary medicine like treating diarrhea (14.3%in cattle and 50% in human) and intestinal pain (35.7%),Diuretic (64.3%), kidney disease and face acne (21.4%). Plant use knowledge varies according to community status and increases with increasing age of respondents. Nitrogen (N), Protein and Ash contents (5.22%, 32.51% and 33.50% respectively) were recorded. Secondary metabolites like phenolics (188.67mg g-1), Alkaloids (8.00mg g-1)and flavonoids (0.35mg g-1)were recorded in the plant on of dry weight basis. Conclusion: Results on nutritive parameters and secondary metabolite prove it to be good as forage for livestock and can be used for medicinal purposes. So, further studies should be conducted to explore its medicinal properties. Key words: Bui, traditional uses, Chemical composition, ethnobotany, Cholistan desert